Bouba/Kiki in Touch: Associations Between Tactile Perceptual Qualities and Japanese Phonemes - Sakamoto, Maki; Watanabe, Junji (Frontiers in Psychology, 2018)
Several studies have shown cross-modal associations between sounds and vision or gustation by asking participants to match pre-defined sound-symbolic words, such as “bouba” or “kiki”, with visual or gustatory materials. Here, we conducted an explorative study on cross-modal associations of tactile sensations using spontaneous production of Japanese sound-symbolic words and semantic ratings. The Japanese language was selected, because it has a large number of sound-symbolic words that can represent a wide range of tactile perceptual spaces with fine resolution, and it shows strong associations between sound and touch. In the experiment, we used 120 everyday materials to cover basic material categories that could be associated with fundamental dimensions of tactile perception. Upon contact with these materials, participants expressed their tactile sensations by using Japanese sound-symbolic words, and at the same time, evaluated the tactile sensations by semantic differential scales using adjective pairs. Thanks to the variety of testing materials, we were able to demonstrate the existence of systematic associations between sounds and tactile fundamental perceptual dimensions in a more detailed and comprehensive way than ever done so before. In particular, we found that for vowels, positive tactile ratings were associated with the back vowel (/u/), while negative ratings were associated with the front vowels (/i/ and /e/). The central vowels (/o/ and /a/) were mainly associated with rough, hard, and dry feelings. Consonants were categorized based on vocal features and articulation. The category of the voiced consonants (e.g., /ʣ/ and /g/) corresponded to feelings of roughness, while that of voiceless consonants (e.g., /ʦ/, and /s/) corresponded to feelings of smoothness. The categories of the bilabial plosive (/p/ and /b/) and voiced alveolar nasal (/n/) consonants were mainly related to soft, sticky and wet feelings, while that of voiceless alveolar affricate (/ʦ/) and voiceless velar plosive (/k/) consonants were related to hard, slippery and dry feelings.